Culture and Thematic Learning: Indonesian Teachers’ Perspectives - Tiyas Abror Huda; Een Yayah Haenilah (Prosiding Seminar Nasional Pendidikan FKIP Universitas Lampung, 2024)
Education and culture are two things that cannot be separated because the inclusion of culture in education will make learning more meaningful. The purpose of this research was to find out the perceptions of elementary school (SD) teachers in Lampung Province regarding the integration of culture in thematic learning in elementary schools. Much research has been conducted on the integration of culture into learning in elementary schools, but this research focuses more on the cultural context in Lampung Province. Data collection was carried out by distributing questionnaires through the Google Form, where the questionnaire had previously been tested for validity and reliability. Then it was strengthened by interviews to dig deeper into integrating culture into learning. Furthermore, the data obtained were analyzed both quantitatively and qualitatively. The research results show that cultural integration in learning can (1) be a learning resource that is parallel to the main material as a form of introducing and preserving culture as early as possible in elementary school, (2) help students achieve their cognitive, affective, and psychomotor competencies, and (3) become additional references for teachers so that learning can be more real for elementary school students because culture is inherent in students' daily lives. (4) Of course, in practice, there are many obstacles faced by teachers, namely limited teacher knowledge related to culture, lack of supporting resources, limited learning time, lack of support from student parents, inadequate facilities, limited ability of teachers to teach children's songs according to the theme, available teaching materials, and still using a subject approach, making it difficult for teachers to combine material according to the theme. Therefore, real collaboration is needed between teachers, school principals, communities, and policymakers to support each other and integrate culture in elementary schools as early as possible.